In vitro methods of germ-plasm conservation - Roca, W.; Chavez, R.; Martin, M.L.; Arias, D.I.; Mafla, G.; Reyes, Raúl (Canadian Science Publishing, 1989)
For many crops with preferential vegetative propagation, or which are sterile, or have seed unresponsive to standard seed storage techniques, in vitro methods can provide a valuable adjunct to other germplasm conservation strategies. Two types of in vitro gene banks are proposed: (i) an in vitro active gene bank where cultures are maintained under slow growth; of the few of these that exist, the cassava (Manihot) in vitro active gene bank of the Centro Internacional de Agricultura Tropical (CIAT) consists of over 4000 clones; (ii) an in vitro base gene bank, where cultures are cryopreserved; at present, none of this type exist. In vitro conservation offers a means of maintaining valuable gene combinations in a small space, protected against pest and disease attack, soil problems, and climatic changes, and with high multiplication potential. The main limitations are inability to regenerate plants of many important crops and the risk of genetic instability of cultures. A joint project of the International Board for Plant Genetic Resources and CIAT is underway to develop an in vitro based set of procedures for handling germplasm, using cassava as a model, with culture maintenance, stability monitoring, and management data bases being considered. Results of recent work on in vitro conservation and related activities, i.e., germ-plasm collection, exchange, and characterization, will be presented and discussed, with special reference to Manihot. (AS)